2016
DOI: 10.1071/hc16008
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for treatment of depression in primary care: a systematic review and meta-analysis

Abstract: INTRODUCTION Evidence for the effectiveness of drug treatment for depression in primary care settings remains limited, with little information on newer antidepressant classes. AIM To update an earlier Cochrane review on the effectiveness of antidepressants in primary care to include newer antidepressant classes, and to examine the efficacy of individual agents. METHODS Selection criteria included antidepressant studies with a randomly assigned placebo group where half or more subjects were recruited from prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…31 For antidepressants, systematic reviews in primary care have shown NNTs of 6-8.5. 40 Effects observed for Emyna meet and exceed these thresholds, suggesting that they are clinically meaningful and comparable to established depression treatments.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…31 For antidepressants, systematic reviews in primary care have shown NNTs of 6-8.5. 40 Effects observed for Emyna meet and exceed these thresholds, suggesting that they are clinically meaningful and comparable to established depression treatments.…”
Section: Discussionmentioning
confidence: 86%
“…Effects can be regarded as clinically relevant when they exceed d = 0.24, and more stringent guidelines suggest that they should exceed d = 0.50 (corresponding to number needed to treat [NNT] = 3.6) . For antidepressants, systematic reviews in primary care have shown NNTs of 6‐8.5 . Effects observed for Emyna meet and exceed these thresholds, suggesting that they are clinically meaningful and comparable to established depression treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Unplanned drop-out from care is an important adverse outcome, since the opportunity to modify treatment to better meet patient needs has been lost. Although important, none of these contextual influences are captured in the measures of symptom severity conventionally used to deliver collaborative care [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cipriani et al [3] did not include mianserin in network meta-analysis [3]. Arroll et al [41] conducted a meta-analysis of two trials in which mianserin was compared with placebo and concluded that mianserin was effective for continuous outcomes but did not affect rates of remission and response [41].…”
Section: Plos Onementioning
confidence: 99%